Study on Physico-Chemical Characteristics of Amorphous Structure of B2O3— CuO Binary System - Fereydoun, Ashrafi; Seid Ahmad, Babanejad; Ali, Modanloo (Asian Journal of Chemistry, 2010)
The B2O3-CuO binary system can form the glass with the percentage combinations of (100-x) B2O3 - (x) CuO, where x < 6. The optical edge absorption for recognizing electronic structure of this binary system has been studied. The samples were prepared from melting and then rapidly cooling of different mixtures of two oxides. The visible spectrum of these specimens in the range of 300-500 nm were characterized. The absorption coefficient α (ω) is obtained by analyzing these spectra. By use of Urbach and Mott and Davis theories and tracing the diagram of (αh ω)1/n vs. α(ω), n = 1 was obtained. By extrapolation traced diagram of (αh ω) vs. h ω, the energy of optical gap, Eopt in (α h ω) = 0, from 1.43 to 2.15 eV was evaluated. Eopt increases with increase of CuO percentages. The constant of proportion B was also evaluated by using Mott-Davis relation. The width of location state ΔE is calculated from the slop of ln α vs. h ω diagram and obtained amounts are from 0.8716 to 3.1056.